2022
DOI: 10.3892/mmr.2022.12701
|View full text |Cite
|
Sign up to set email alerts
|

CTRP9 decreases high glucose‑induced trophoblast cell damage by reducing endoplasmic reticulum stress

Abstract: c1q/TnF-α-related protein 9 (cTrP9) is downregulated in gestational diabetes mellitus (GdM) and may exert a protective effect against GdM, although its mechanism of action is yet to be elucidated. To investigate the specific role of cTrP9 in GdM, the human placental trophoblast cell line HTr8/SVneo was treated with high glucose (HG) to simulate the environment of GdM in vitro. The effects of cTrP9 on the HTr8/SVneo cells and endoplasmic reticulum (er) stress were analyzed before and after cTrP9 overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Prior research has supported our observations. For instance, it has been reported that CTRP9, when applied to high glucose‐induced HTR8/SVneo cells, enhances cell viability by mitigating ERS, ultimately ameliorating gestational diabetes mellitus 32 . Additionally, Yoshida et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has supported our observations. For instance, it has been reported that CTRP9, when applied to high glucose‐induced HTR8/SVneo cells, enhances cell viability by mitigating ERS, ultimately ameliorating gestational diabetes mellitus 32 . Additionally, Yoshida et al.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been reported that CTRP9, when applied to high glucose-induced HTR8/SVneo cells, enhances cell viability by mitigating ERS, ultimately ameliorating gestational diabetes mellitus. 32 Additionally, Yoshida et al proposed that TM administration significantly hampers HTR8/Svneo cell invasion, underscoring the potential of ERS to suppress EVT invasion capability and promote hypertensive disorders of pregnancy. 33 These studies further corroborate the significance of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that an over‐activated ERS is the primary cause of abnormal trophoblast differentiation and placental development in patients with PE (Capatina et al, 2021). Inhibition of ERS has been shown to reduce trophoblast damage (Zhang et al, 2022). In the present study, we found that hypoxic stimulation decreased trophoblast viability but promoted inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…TM is a classical ER stress inducer [12]. HTR-8/SVneo cells were induced with DMSO and 0.078 µg/ml TM, respectively [13][14]. ELISA revealed that the expression level of Aβ 1−42 was enhanced in TM-induced HTR-8/SVneo cells (Fig.…”
Section: Cell Autophagy and Upregulation Of Aβ 1−42 Induced By Er Stressmentioning
confidence: 90%